Casts of an Island - Antoniou, Klitsa (My University, 2026)
Casts of an Island Artwork selection and exhibition curation by Nicos Chr. Pattichis Exhibition Duration: November 9th to November 30th Location: Mercedes-Benz Strovolos CYCO (Cyprus Contemporary Art Center) Nicosia, Cyprus